Mitophagy Dynamics in Caenorhabditis elegans - Palikaras, K.; Lionaki, E.; Tavernarakis, N. (Methods Mol Biol, 2019)
Mitochondrial selective autophagy (mitophagy) is a critical cellular process for mitochondrial homeostasis and survival both under basal and stress conditions. Distinct cell types display different requirements for mitochondrial turnover depending on their metabolic status, differentiation state, and environmental cues. This points to the necessity of developing novel tools for real-time, tissue-specific assessment of mitophagy. Caenorhabditis elegans is an invaluable model organism for this kind of analysis providing a platform for simultaneous monitoring of mitophagy in vivo in different tissues and cell types, during development, stress conditions, and/or throughout life span. In this chapter we describe three versatile, noninvasive methods, developed for monitoring in vivo early and late mitophagic events in body wall muscles and neuronal cells of C. elegans. These procedures can be readily used and/or provide insights into the generation of novel imaging methods to investigate further the role of mitophagy at the organismal level under normal and pathological conditions.
Keywords: *Aging; *Autophagosome; *Autophagy; *Caenorhabditis elegans; *DsRed; *Fluorescent microscopy; *Green Fluorescent Protein (GFP); *Lysosomes; *Mitochondria; *Mitophagy; *mtRosella; Animals; Animals, Genetically Modified; Biological Assay/instrumentation/*methods; Caenorhabditis elegans Proteins/genetics/metabolism; Caenorhabditis elegans/physiology; Electron Transport Complex III/genetics/metabolism; Genes, Reporter/genetics; Image Processing, Computer-Assisted/instrumentation/methods; Intravital Microscopy/instrumentation/*methods; Luminescent Proteins/genetics/metabolism; Microscopy, Fluorescence/instrumentation/methods; Microtubule-Associated Proteins/genetics/metabolism; Mitochondria/metabolism; Mitophagy/*physiology; Models, Animal; Muscles/cytology/metabolism; Neurons/metabolism